MOTIVASI KERJA BIROKRAT DALAM MENINGKATKAN PELAYANAN MASYARAKAT PADA BAGIAN KESEJAHTERAAN RAKYAT DAN KEMASYARAKATAN SEKRETARIAT DAERAH KABUPATEN PARIGI MOUTONG - Aidar, Aidar (Katalogis, 2013)
This research was conducted with the purpose of analyzing the bureaucrat working motivation on People Welfare Division and Region Secretariat Society Parigi Moutong Region and the barrier factors. This research was a qualitative descriptive research that using Abraham Maslow needs hierarchy theory. The phenomena observed was physical needs, safety needs, social needs, reward and self-actualization needs. The informants of the research were the staffs on Social and Welfare Division who worked for many years and also the other officers with senior degree. The data used was the primary data which directly obtained from the informants that then was compared to secondary data with the technique of data collection done through interview, observation and documentation. Next, the data analysis done in the stage of data reduction, data display and drawing conclusion. The research result found that there was a difference between ideal value and the fact in the field so that it was concluded that seen from physical needs part then the income obtained was not very appropriate if faced by the recent life needs; safety needs was not ful, filled because the minimum facilities; social needs was not fulfilled caused by the officer interaction did not run well as well as the reward and self-actualization needs.